2002
DOI: 10.1046/j.1365-2362.2002.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory imbalance between IL‐10 and TNFα in unstable angina potential plaque stabilizing effects of IL‐10

Abstract: Patients with unstable angina appear to have an imbalance between TNFalpha and IL-10, possibly favouring inflammatory net effects. IL-10 may have beneficial effects on mechanisms that are important in plaque rupture and thrombus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 30 publications
3
63
1
3
Order By: Relevance
“…Thus, it has been shown that the marked rise in inflammatory cytokines during ACS is not accompanied by elevation of the anti-inflammatory cytokine IL-10. 16,17 In the present study, we show a similar pattern in the balance between IL-1 and the naturally occurring antagonist IL-1Ra, with markedly increased mRNA levels of IL-1␣ and IL-1␤ in circulating mononuclear leukocytes in both stable and particularly in unstable angina, accompanied by only modestly increased IL-1Ra levels in the unstable patients. Hence, although IL-1 is highly inflammatory and potentially plaque-destabilizing, for example by inducing adhesion molecules, clotting factors, chemokines, and matrix metalloproteinases, IL1Ra may protect against those deleterious IL-1 effects.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, it has been shown that the marked rise in inflammatory cytokines during ACS is not accompanied by elevation of the anti-inflammatory cytokine IL-10. 16,17 In the present study, we show a similar pattern in the balance between IL-1 and the naturally occurring antagonist IL-1Ra, with markedly increased mRNA levels of IL-1␣ and IL-1␤ in circulating mononuclear leukocytes in both stable and particularly in unstable angina, accompanied by only modestly increased IL-1Ra levels in the unstable patients. Hence, although IL-1 is highly inflammatory and potentially plaque-destabilizing, for example by inducing adhesion molecules, clotting factors, chemokines, and matrix metalloproteinases, IL1Ra may protect against those deleterious IL-1 effects.…”
Section: Discussionsupporting
confidence: 76%
“…Second, previous studies of human atherosclerotic plaques have revealed an inverse association between the presence of IL-10 and TUNEL staining, supporting a link between IL-10 and decreased apoptosis (34), and such an association has also recently been demonstrated in LDL-receptor mice overexpressing IL-10 (35). Finally, although several studies have shown increased levels of inflammatory cytokines such as TNF␣ in ACS, we and others have recently reported normal IL-10 levels in these patients, suggesting an inflammatory imbalance (6,(36)(37)(38). However, the clinical consequences of the IL-10-mediated enhancement of foam cell formation is far from clear and will need to be further elucidated before any firm conclusion can be drawn.…”
Section: The Effect Of Il-10 On Foam Cells In Human Atherosclerotic Dmentioning
confidence: 64%
“…Thus, studies in IL-10-transgenic and IL-10-deficient mice models suggest an important protective role for this cytokine in both the formation and the stabilization of atherosclerotic lesions (2,4,5). Moreover, we have recently shown that IL-10 inhibits the release of inflammatory cytokines, tissue factor, and matrix metalloproteinases from periph-eral blood mononuclear cells (PBMCs) in patients with ACS, potentially promoting plaque stabilization (6). However, the exact mechanisms of action of IL-10 in atherogenesis have not been fully clarified and its role in plaque stabilization is far from clear.…”
mentioning
confidence: 99%
“…8A, which is published as supporting information on the PNAS web site). TNF concentrations of this level (Ϸ5 ng͞ml) have been reported in animal models of inflammation and atherosclerosis and also in clinical studies (23,24). The synergistic effect was observed over a range of TNF concentrations, up to 20 ng͞ml, that have been reported to be effective in the activation of endothelial cells (Fig.…”
Section: Tf Induction By Proinflammatory Cytokines Tnf Il-1␤ and Cmentioning
confidence: 68%